Child Growth and Development Education in Sei Tuan Village - Dior Manta Tambunan; Mhd. Taufik Daniel Hasibuan; Jenita T. L. Halawa; Anisa T. A. Simamora; Dewi V. Lumbanraja; Dina Silaban; Elsa R. Silalahi; Gabriel K. Rumapea; Hasnida Situmeang; Karin Aulia; Karolus K. Agustus; Marsinta Ambarita; Qory A. Rahayu; Revah S. Parhusip; Robintang Hutasoit; Rosen O. Siburian; Siti Zahraini; Swan S. A. P. Duha; Yunike Agne Marbun (International Journal of Community Service Implementation, 2026)
Growth and developmental issues in toddlers are often not detected early because some parents perceive developmental delays as a normal process that will improve with age. Delayed detection leads to delayed intervention, which can decrease the chances of successful treatment. Therefore, parent’s education is crucial and urgent. This activity was carried out by lecturer with students from the Bachelor in Nursing Science Study Program, Murni Teguh University at the Integrated Health Post in Sei Tuan Village and attended by 42 mothers who have toddlers. The enthusiasm of mothers for the program was evident in the lively Question & Answer session. The majority of mother’s ages are 26-30 years old were 24 respondents (57.2%). The majority of mother’s education levels are elementary school are 14 respondents (33.3%) and junior high school are 13 respondents (30.9%). The majority of mother’s occupations are laborers and farmers, with 13 of each occupation representing 30.9%.